The bio-immobilization of Pb(II) induced by the Chlorella–montmorillonite composite in the Ca(II) environment - Wang, Zhen; Chen, Jinhui; Tan, Jiaqi; Lu, Zijing; Wang, Xizhuo; Jianbo Li (Frontiers in Environmental Science, 2022)
The clay-microbial consortium was ubiquitous in the soil near the mining area and played an important role in the transport of heavy metals. In this study, Chlorella sorokiniana FK were separated from Lead-zinc mine tailings. The montmorillonite-Chlorella sorokiniana FK system as a typical case was applied to study Pb(II) bio-mineralization in the presence of usually co-existent Ca(II), and further reduce the migration and transformation of Pb(II) in Ca(II) environment. Chlorella sorokiniana FK has shown good resistance to Pb(II) and the addition of montmorillonite provided a more stable pH environment, which is conducive to the stability of Pb(II)-bearing bio-minerals. Montmorillonite creates a low-biotoxicity environment in the overall process, especially less Pb(II) bio-adsorption capacity of individual Chlorella to protect the process of mineralization effectively. Batch experiment results also demonstrated that montmorillonite as the formation site of bio-minerals results in dispersed minerals on the surface of Chlorella and Chlorella-MMT composite, which is beneficial to the survival of Chlorella. Moreover, Pb(II)-bearing phosphate minerals tended to form in the Ca(II) environment rather than without Ca(II). This study demonstrated the mechanism of Pb(II) immobilization induced by Chlorella in the Ca(II) environment, further presenting a green, sustainable, and effective strategy for Pb(II) bio-immobilization combining clay minerals and microorganisms.